Verbal Tactics of Implementing Discrediting Strategy in the U.S. Diplomatic Discourse - Sudus, Yuliia (East European Journal of Psycholinguistics, 2016)
The article presents the analysis of the accusation tactics that implement a discrediting strategy in the English diplomatic discourse. The aim of the article is to study speech act formations in tactics of accusation that implement a discrediting strategy. The object of the study is tactics of accusation, which implement the discrediting strategy in diplomatic discourse. The article offers a classification of markers of the communicative tactics of accusation that implement a discrediting strategy in the public statements of US diplomats, namely V. Nuland, G. Pyatt, S. Power, D. Baer, relating to the military conflict in eastern Ukraine. The total number of public speeches that have been analyzed is 97 (from 2013 to 2015). Attention is drawn primarily to the speech acts and how they implement the tactics of accusation in DD. The author has found that the tactics of accusation is basic and the most common tactics of implementing the discrediting strategy in the studied speeches. At the core of these tactics are mainly direct assertive speech acts. ReferencesАлєксєєва І. О. Конфронтаційні тактики міжособистісного конфлікту (на матеріаліангломовної комунікації) / І. О. Алєксєєва // Лінгвістика ХХІ століття: нові дослідження іперспективи. − К. : Логос, 2012. − С. 21–30.Alekseyeva I. (2012). Konfrontatsiyni taktyky mizhosobystisnoho konfliktu (na materialianhlomovnoyi komunikatsiyi). [Confrontational tactics of interpersonal conflict (on thematerial of English communication)], Lingvistyka ХХІ Stolittya: Novi Doslidzhennya iPerspektyvy, 21–30.Егорова Е. Н. Речевая агрессия и стратегия дискредитации (на примере анализа газетныхпубликаций) [Электронный ресурс] / Е. Н. Егорова // Язык и текст. – Т. 2. − № 3. –C. 69–75.Yegorova, Ye. (2015). Rechevaya ahressyya y stratehyya dyskredytacyy (na prymere analyzahazetnыx publykacyj). [Speech aggression and strategy of discrediting (based on the analysis ofnewspaper articles)], Yazyk i Text, 2(3), 69–75.Михалева О. Л. Политический дискурс: способы реализации агональности [Электронныйресурс] / Л. О. Михалева. – Режим доступа: http://rus-lang.isu.ru/about/group/mikhaleva/state2/Myhaleva O. (2012). Polytycheskyj dyskurs: sposoby realyzacyy ahonalnosty. [Politicaldiscourse: means of agonal implementation]. Retrieved from http://ruslang.isu.ru/about/group/mikhaleva/state2/ Кемерово, 2004.Myhaleva O. (2004). Polytycheskyj dyskurs kak sfera realyzacyy manypulyatyvnohovozdejstvyya. [Political discourse as the scope of the implementation of the manipulativeinfluence]. Ph.D. dissertation summary. Kemerovo.Пальшина О. М. Лінгвістичні та психологічні аспекти вивчення комунікативноїповедінки мовця: категорії, теорії, персоналії / О. М. Пальшина // Studia Linguistica. −2012. − Вип. 6(2). − С. 329–337.Palshyna O. (2012). Lingvistychni ta psyholohichni aspekty vyvchennya komunikatyvnoyipovedinky movcya: katehoriyi, teoriyi, personaliyi. [Linguistic and Psychological Aspects ofcommunicative behavior of the speaker: categories, theories, personalities]. Studia Linguistica,6(2), 329–337.Славова Л. Л. Мовна особистість політика: когнітивно-дискурсивний аспект :монографія / Л. Л. Славова. – Житомир, 2010. – 358 с.Slavova, L. (2010). Movna osobystist polityka: kohnityvno-dyskursyvnyj aspekt. [Languageidentity of the politician: cognitive-discursive aspect], Zhytomyr: Zhytomyr State University.